Thiamin supplementation does not reduce the frequency of adverse events after anti-malarial therapy among patients with falciparum malaria in southern Laos. - Mayxay, M; Khanthavong, M; Cox, L; Sichanthongthip, O; Imwong, M; Pongvongsa, T; Hongvanthong, B; Phompida, S; Vanisaveth, V; White, N; Newton, P (BioMed Central, 2014)
BACKGROUND: In a recent study one third of Lao patients presenting with uncomplicated Plasmodium falciparum malaria had biochemical evidence of thiamin deficiency, which was associated with a higher incidence of adverse events. Thiamin supplementation might, therefore, reduce adverse events in this population. METHODS: An exploratory, double-blind, parallel group, placebo-controlled, superiority trial of thiamin supplementation in patients of all ages with uncomplicated and severe falciparum malaria was conducted in Xepon District, Savannakhet Province, southern Laos. Patients were randomly assigned to either oral thiamin 10 mg/day for 7 days immediately after standard anti-malarial treatment then 5 mg daily until day 42, or identical oral placebo. RESULTS: After interim analyses when 630 patients (314 in thiamin and 316 in placebo groups) had been recruited, the trial was discontinued on the grounds of futility. On admission biochemical thiamin deficiency (alpha ≥ 25%) was present in 27% of patients and 9% had severe deficiency (alpha > 31%). After 42 days of treatment, the frequency of thiamin deficiency was lower in the thiamin (2%, 1% severe) compared to the placebo (11%, 3% severe) groups (p < 0.001 and p = 0.05), respectively. Except for diarrhoea, 7% in the placebo compared to 3% in the thiamin group (p = 0.04), and dizziness on day 1 (33% vs 25%, p = 0.045), all adverse events were not significantly different between the groups (p > 0.05). Clinical, haematological, and parasitological responses to treatment did not differ significantly between the two groups. CONCLUSION: Thiamin supplementation reduced biochemical thiamin deficiency among Lao malaria patients following anti-malarial drug treatment, but it did not reduce the frequency of adverse events after anti-malarial therapy or have any detected clinical or parasitological impact. TRIAL REGISTRATION: ISRCTN 85411059.